Feed pellet production with locally availably products - Rudiger, Udo; Idoudi, Zied; Dhehibi, Boubaker; Tebourbi, Ons; Shiri, Zahra; Souissi, Asma (CGIAR System Organization, 2024)
Compressing local agro-industrial by-products into nutrient-dense livestock feed pellets is a worthwhile innovation to compete with expensive and imported feed pellets or concentrates. The use of such pellets also alleviates pressure on rangelands or grasslands. This innovation consists of a small scale compressor ‘pelletizer’ and formulas to create qualitatively sufficient feed pellets with locally available inputs. In Tunisia, there are many agro-pastoralists that are dependent on expensive and imported livestock feed pellets to improve livestock quality and to supplement feed shortages. Risks of relative feed shortages are likely to increase due to climate change. Also, there are many discarded by-products from local agro-food supply chains such as olive cakes, date kernels, and downgraded dates, which still contain nutrients. Feed pellet production with this small-scale pelletizer producing 500 kg pellets/hour is also an interesting income-generating activity for farmer organizations and creates employment.